Use of Limberg Flap for Closure of Sacral Pressure Sores - Avtar Singh; K S Mander; G P Singh; S K Gulati; Gopal Malhotra; K C Garg; J P S Walia (Indian Journal of Plastic Surgery)
Limberg flap has been used for the closure of moderate size sacral pressure sores in 5 cases. It provides a good padded skin cover with the suture line away from the midline which is the area of ulceration. No breakdown or ulceration in the flap or donor defect suture line were seen during 1-4 years of follow up. Operative technique is briefly described and important points on flap planning are discussed.